Cultural pessimism : narratives of decline in the postmodern world - Bennett, Oliver (Edinburgh University Press, 2001)
This text shows how cultural pessimism can be related to the cumulative effect of our key narratives of decline - environmental decline, moral decline, intellectual decline and political decline.